Frequency of occurrence of urinary tract infection in double j stented versus non-stented renal transplant recipients - Durre Shohab; Athar Khawaja; Emad Atif; Imran Jamil; Iftikhar Ali; Saeed Akhter (Saudi Journal of Kidney Diseases and Transplantation, 2015)
Prophylactic ureteric stenting in renal transplant recipients prevents major surgical complications such as ureteric leak and obstruction on the one hand while, on the other hand, it is associated with complications like urinary tract infections (UTI), hematuria, stent migration, stent encrustation and forgotten stents. UTI is documented to be most common complication associated with double J (DJ) stent. In this retrospective observational study involving 157 patients, we compared the frequency of occurrence of UTI in DJ-stented versus non-stented renal transplant recipients. The study patients had undergone renal transplantation, with or without DJ-stenting, between January 2007 and June 2012. The mean age of the study subjects was 34.01 ± 14.63 years. The patients were followed-up for one year post-transplantation with regular evaluation, including detailed assessment, complete blood picture, renal function tests, routine urine examination and cultures. Data were collected through chart and electronic record review. Of a total of 157 patients, 61 (38.85%) developed UTI, including 30 of 74 stented patients (40.54%) and 31 of 83 non-stented renal transplant recipients (37.34%). Relative risk was calculated to be 1.08. The mean serum creatinine at the end of one year was 1.47 mg/dL in DJ-stented patients and 1.36 mg/dL in nonstented patients. Our study suggests that there is no significant difference in the frequency of UTI between DJ-stented and non-stented renal transplant recipients.